PIPE - PROGRAM OF SPECIFIC INTERVENTION PSYCHOMOTRICITY (Fiep Bulletin - online, 2014)
The development of children with Down syndrome (SD) passes for a constant process of transformation, disclosing delays in the motor acquisitions. From zero the three years generally these children receive stimulation in specialized centers; however, to leave of this age, the stimulation reduces considerable or even though it ceases. The objective of this research is to present the proposal of the Program of Specific Psychomotricity Intervention (PIPE) for children with SD of 04 the 12 years offered by the Laboratory of Human Development (LADEHU) of the Center of Physical Education, Physiotherapy and Deports (CEFID) of the University of the State of Santa Catarina (UDESC) and to analyze the results of one year of intervention in a group of children. For in such a way, 4 children had been selected intentionally who had participated since the beginning of the project in 2005 and had appeared, at the very least, 15 sessions in 1º semester of 2006. These children had been evaluated at three moments, semester, always for the same appraiser. One used for this the tests that compose Motor Development Scale - "EDM" (PINK GRANDSON, 2002), that it evaluates the following areas: fine motricity, global motricity, balance, corporal project, space organization, secular organization and laterality. Between the evaluations, the children had participated of sessions of "Psicomotora Intervention", carried through two times per week, with duration of 50 minutes and offered interdisciplinarmente for professionals of the areas of the health and education. The daily accompaniment of the interventions was made through a Model of Comment (SÁNCHES et al, 2003). Our results show to evolution in the motor development of all the children, after to participate of the PIPE per one year. The positive aspect of the directed interventions was evident in this research the children with Down syndrome.
Keywords: Motor assessment; Psychomotricity intervention; Down syndrome